True blood. The complete seventh season [videorecording (DVD)] - Ball, Alan, 1957- (HBO Home Entertainment, 2014)
The seventh and final season of this supernatural drama series from HBO. In the end, some of True Blood₂s most beloved figures will meet cruel fates, while others will cheat death (true and otherwise) to forge happily-ever-after relationships that will leave fans surprised and, ultimately, satisfied.